1998
DOI: 10.2220/biomedres.19.127
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Therapeutic Efefcts of a Chinese Herbal Prescription in Streptozocin-Treated Rats

Abstract: A Chinese herbal prescription, Hachimzjiogan, is one of the traditional Kampo prescriptions in Japan and China, and has been widely used for treatment of several chronic disease including diabetes mellitus. The present study provides experimental evidence for significant lowering of the streptozocin (STZ)-induced increase in plasma glucose level, and for significant recovery to the intact levels of plasma insulin and C-peptide in the STZtreated rats after treatment for four weeks with the prescription. Signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Therefore, the increases in serum and pancreatic IRI levels due to HJ were attributable to increased insulin synthesis or secretion by residual b cells after STZ administration, but not to differentiation and proliferation of residual pancreatic b cells. In other words, while the present study's results differed in some respects from those of Luo and colleagues, 5) increases in IRI levels by HJ are not due to quantitative changes in pancreatic b cells, and HJ does not repair pancreatic b cells damaged by STZ. The present study clarified that HJ increases IRI levels by elevating insulin synthesis and secretion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increases in serum and pancreatic IRI levels due to HJ were attributable to increased insulin synthesis or secretion by residual b cells after STZ administration, but not to differentiation and proliferation of residual pancreatic b cells. In other words, while the present study's results differed in some respects from those of Luo and colleagues, 5) increases in IRI levels by HJ are not due to quantitative changes in pancreatic b cells, and HJ does not repair pancreatic b cells damaged by STZ. The present study clarified that HJ increases IRI levels by elevating insulin synthesis and secretion.…”
Section: Discussioncontrasting
confidence: 99%
“…As to the therapeutic effects of HJ, various human and animal studies have been conducted, [2][3][4][5] most of which examined the effects of HJ on renal damage and the action mechanism for such effects. [6][7][8] Experimentally, HJ has exhibited beneficial effects in patients with diabetes mellitus and in many diabetic animal models, and in particular, it is used in the treatment of dry mouth, thirst, and polyuria associated with diabetes.…”
mentioning
confidence: 99%
“…8,9) It is reported that one of the traditional Kampo prescriptions, namely, Hachimi-jio-gan (HJ), has an antidiabetic action that ameliorates hyperglycemia and protects against diabetic nephropathy in experimental diabetic model rats. 10,11) In this study, we examined the eŠects of HJ on intestinal function using streptozotocin (STZ)-induced diabetic model rats. The sucrase and maltase activities in the intestinal mucosa were measured as indices of digestive function measurement, and the mucosal weights, DNA contents and plasma Glucagon-like peptide 2 (GLP-2) levels were measured as indices of intestinal mucosa proliferation.…”
Section: Introductionmentioning
confidence: 99%